REGULAR SURVEILLANCE OF HIGHWAY BRIDGE USING SENSOR - k. , vamsi; P. , Jagadeesh (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of constructing bridges is to connect two locations that are separated by nature, like the sea, water, railway tracks, lowlands, etc. If any cracks or damages occur in the bridges, it leads to severe problems. Because a huge number of vehicles are using the bridges and flyovers daily, monitoring has to be done accordingly in order to increase the life time of the bridge. The bridge or flyover transportation structure is rapidly damaged. Bridge engineers want to continuously monitor and maintain the bridge to ensure the safety of the public. In olden days, the traditional method of visually checking was used. These methods lead to an expensive and time-consuming process. The quality of the bridges is measured based on their outer appearance. The internal damages are not found out by using traditional methods. This proposed system is used to monitor the bridges continuously by using current communication technologies like GSM. The main advantage of this proposed system is easily identifying the cracks or damages that occur in inside and outside of the bridge